Angiotensin-II-dependent Hypertension Requires Cyclooxygenase 1-derived Prostaglandin E(2) and EP(1) Receptor Signaling in the Subfornical Organ of the Brain - Cao, Xian (2012)
Cyclooxygenase (COX)-derived prostanoids have long been implicated in blood pressure (BP) regulation. Recently prostaglandin E(2) (PGE(2)) and its receptor EP(1)R have emerged as key players in angiotensin II (Ang-II)-dependent hypertension (HTN) and related end-organ damage. However, the enzymatic source of PGE(2), ie COX-1 or COX-2, and its site(s) of action are not known. The subfornical organ (SFO) is a key forebrain region that mediates systemic Ang-II-dependent HTN via reactive oxygen species (ROS). We tested the hypothesis that cross-talk between PGE(2)/EP(1)R and ROS signaling in the SFO is required for Ang-II HTN. Radiotelemetric assessment of BP revealed that HTN induced by infusion of systemic “slow-pressor” doses of Ang-II was abolished in mice with null mutations in EP(1)R or COX-1 but not COX-2. Slow-pressor Ang-II-evoked HTN and ROS formation in the SFO were prevented when the EP(1)R antagonist SC-51089 was infused directly into brains of wild-type mice, and Ang-II-induced ROS production was blunted in cells dissociated from SFO of EP(1)R(−/−) and COX-1(−/−) but not COX-2(−/−) mice. In addition, slow-pressor Ang-II infusion caused a ~3-fold increase in PGE(2) levels in the SFO but not in other brain regions. Finally, genetic reconstitution of EP(1)R selectively in the SFO of EP(1)R-null mice was sufficient to rescue slow-pressor AngII-elicited HTN and ROS formation in the SFO of this model. Thus, COX-1-derived PGE(2) signaling through EP(1)R in the SFO is required for the ROS-mediated HTN induced by systemic infusion of Ang-II, and suggests that EP(1)R in the SFO may provide a novel target for antihypertensive therapy.